Involving students and prospective mathematics teachers through the use of the Think Pair Share design: The impact on increasing students' activeness and learning outcomes in plane geometry - Taufan, Mochammad; Dejarlo, Jenisus O.; Rosa, Adila Juliana; Hidayat, Rahmat; Sunanto, Eko (International Journal of Didactic Mathematics in Distance Education, 2024)
This research aims to determine the increase in student activity and learning outcomes in flat building materials through the use of the think pair share (TPS) design. The research design used to achieve the objectives of this research was classroom action research conducted at SMP Negeri 1 Indramayu. Apart from that, the subjects in this research were 32 students in class VII B, while the instruments used in this research were student observation sheets which aimed to measure activity and formative tests given each cycle. Next, deep data analysis study uses pattern study quantitative descriptive for measure enhancement results Study mathematics students through test formative and measuring enhancement activities carried out every cycle. The results of data processing on learning outcomes obtained an average of 65.09 for cycle I, cycle II of 74.07, and cycle III of 80.45. Likewise, the increase in the number of students reaching completeness Study that is from cycle I as much 5 students out of 32 students or 22%, cycle II as many as 15 students out of 31 students or 47% of the criteria high completeness, and in cycle III there were 26 students out of 31 students or 81% included in the category the criteria for completeness are very high. Next, based on the results of data processing of student activity during the learning process obtained that cycle I had not reached the active category (A) (24 students out of 32 were inactive or 25% from target 75% so cycle I Not yet reach category active). In Cycle II there was an increase from Cycle I to reach the active category (A), namely 20 students were active in the learning process and 11 students were still not actively involved in the learning process. Additionally, in Cycles III there was a significant increase in reaching the active category (A), namely, there were 25 students, or 81% of students involved in the learning process, while the rest were still not active. This matter shows that using the Think Pair Share (TPS) design through the involvement of students and mathematics teachers can increase student activity and learning outcomes in plain material.